PERAN BANTUAN HUKUM DALAM PROSES PERADILAN PIDANA DI KABUPATEN BLORA - Ahmad Muntolib; Sri Endah Wahyuningsih (UNISSULA Semarang, 2018)
The purpose of this law is to know the role of legal aid for suspects / defendants criminal court in Blora Cityt. This legal research is an empirical legal research or descriptive field research. Research location at the Blora City Court, Blora Legal Aid Institute, and Blora Advocate Office. Collection techniques were conducted through interviews directly to the POSBAKUM Chairman of the Blora Court, Advocate interviews, and LBH, and literature study. Based on the research, it was found that the role of legal aid in Blora Regency consisted of providing free legal aid ( prodeo) and providing legal aid not free of charge. Provision of legal aid for the poor who are affected, especially the criminal, the District Court is obliged to provide a legal counsel as defender if it is unable to be financed by the government.Keyword : Legal aid, Criminal Justice,Law